2007
DOI: 10.1002/arch.20225
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of CYP6A5 and CYP6A5v2 in pyrethroid‐resistant house flies, Musca domestica

Abstract: Two cytochrome P450 alleles, CYP6A5 and CYP6A5v2, were isolated from a pyrethroid-resistant house fly stain, ALHF. The two alleles shared 98% similarity in amino acid sequence. To understand the importance of these two alleles in resistance and examine the expression profile of the two alleles between resistant and susceptible strains, quantitative real-time PCR (qRT-PCR) was performed and compared with the Northern blot analysis. We found that qRT-PCR was an efficient method to characterize the expression pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 46 publications
2
42
0
Order By: Relevance
“…quinquefasciatus was examined because these genes overexpressed not only in resistant insects but also in adult stages. Although the expression of CYP6A5v2 was observed to be significantly higher in the abdominal tissue in both the susceptible CS and aabys flies and the resistant ALHF flies compared with their head+thorax tissues, this overexpression was far greater in both sets of tissues for resistant ALHF flies than in the tissues of susceptible flies (Zhu and Liu 2008). The expression of CYP6A36 was not significantly different between the head+thorax and abdomen tissues of the CS strain; lower in the head+thorax tissue than in the abdomen tissue of ALHF; and significantly higher in both tissues of the ALHF strain than in the CS strain (Zhu et al 2008a).…”
Section: Constitutive Overexpression Of P450 Genes In Pyrethroid Resimentioning
confidence: 83%
See 3 more Smart Citations
“…quinquefasciatus was examined because these genes overexpressed not only in resistant insects but also in adult stages. Although the expression of CYP6A5v2 was observed to be significantly higher in the abdominal tissue in both the susceptible CS and aabys flies and the resistant ALHF flies compared with their head+thorax tissues, this overexpression was far greater in both sets of tissues for resistant ALHF flies than in the tissues of susceptible flies (Zhu and Liu 2008). The expression of CYP6A36 was not significantly different between the head+thorax and abdomen tissues of the CS strain; lower in the head+thorax tissue than in the abdomen tissue of ALHF; and significantly higher in both tissues of the ALHF strain than in the CS strain (Zhu et al 2008a).…”
Section: Constitutive Overexpression Of P450 Genes In Pyrethroid Resimentioning
confidence: 83%
“…In addition, some insect P450 genes can be induced by exogenous compounds. Recently, our group has identified that multiple P450 genes are overexpressed in insecticide resistant house flies Musca domestica and mosquitoes Culex quinquefasciatus through both constitutive overexpression and induction by pyrethroids ( (Zhu and Liu 2008;Zhu et al 2008a;b;Liu et al 2011), suggesting that constitutive overexpression and induction are key factors for increased levels of detoxification of insecticides and insecticide resistance. Nevertheless, although their importance in insect physiology and toxicology is widely recognized, there are enormous gaps in our knowledge of insect P450s.…”
Section: P450-mediated Pyrethroid Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…However, variants of the same P450 gene could also respond differently to insecticide pressure. The genes CYP6A5 and CYP6A5v2 have a protein sequence identity of 99% and according to Zhu & Liu (2008), while CYP6A5v2 was over-expressed in a pyrethroid resistant strain of house fl y compared to a susceptible strain, there was no signifi cant difference in expression of CYP6A5 in both strains. There was also a remarkable difference in the expression levels of two genes, CYP4D42v1 (3.2-fold) and CYP4D42v2 (7.0-fold) in permethrin selected Culex quinquefasciatus assessed using qPCR (Reid et al, 2012).…”
Section: Discussionmentioning
confidence: 98%